Evolution of an expanded mannose receptor gene family. - Karen Staines; Lawrence G Hunt; John R Young; Colin Butter (PLoS ONE, 2014)
Sequences of peptides from a protein specifically immunoprecipitated by an antibody, KUL01, that recognises chicken macrophages, identified a homologue of the mammalian mannose receptor, MRC1, which we called MRC1L-B. Inspection of the genomic environment of the chicken gene revealed an array of five paralogous genes, MRC1L-A to MRC1L-E, located between conserved flanking genes found either side of the single MRC1 gene in mammals. Transcripts of all five genes were detected in RNA from a macrophage cell line and other RNAs, whose sequences allowed the precise definition of spliced exons, confirming or correcting existing bioinformatic annotation. The confirmed gene structures were used to locate orthologues of all five genes in the genomes of two other avian species and of the painted turtle, all with intact coding sequences. The lizard genome had only three genes, one orthologue of MRC1L-A and two orthologues of the MRC1L-B antigen gene resulting from a recent duplication. The Xenopus genome, like that of most mammals, had only a single MRC1-like gene at the corresponding locus. MRC1L-A and MRC1L-B genes had similar cytoplasmic regions that may be indicative of similar subcellular migration and functions. Cytoplasmic regions of the other three genes were very divergent, possibly indicating the evolution of a new functional repertoire for this family of molecules, which might include novel interactions with pathogens.